Jointless Bridge Decks - Wasserman, Edward P. (Engineering Journal, 1987)
Todays bridge designer is striving essentially to achieve the same goals as his counterparts were 50 years ago: long term serviceability, low maintenance characteristics and economy of construction. While we have mastered new techniques such as welding, composite decks, hybrid girders, load factor and autostress designs, we still cling to many of the old ideas that lessen the potential for achieving our goals. One of the more important aspects of design, the reduction or elimination of roadway expansion devices and associated expansion bearings is overlooked consistently, or avoided. Contractors, engineers, producers and fabricators of steel bridges should examine the possibilities for minimum or no joint structures to provide your clients the most durable and cost-effective product, as well as to remain competitive, as an industry, with alternate design materials.